Effects of physically effective neutral detergent fiber content on dry matter intake, digestibility, and chewing activity in Korean native goats (Capra hircus coreanae) fed with total mixed ration - Jang, Se Young (Asian-Australasian journal of animal sciences, 2017)
OBJECTIVE: This experiment was to determine proper physical traits in the diet for goats by investigating the effects of physically effective neutral detergent fiber (peNDF) content on dry matter intake (DMI), digestibility, and chewing activity in black goats fed with total mixed ration (TMR)